The Dark Side of Leadership: Examining Toxicity, Narcissism and Abusive Practices in Modern Organizations (Journal of Asian Development Studies, 2025)
This paper further elaborates the disadvantages of poor leaders, narcissism, and abusive attitudes in the current organizations with the view of exploring the impact of the abusive practices on the welfare of the employees, job satisfaction, turnover intention, and workplace stress. This paper is grounded on the mixed-methodology, and its data collection methods (qualitative and quantitative) are integrated. They conducted an entire survey of 500 employees (non-systematic) and discovered that the correlations between these leadership behaviors and unfavorable outcomes of the organization were high. There was also relationship between toxic leadership and low employee morale and low productivity, and narcissistic leadership that encouraged a competitive, egocentric environment basing on the decision-making level based on immorality. Abuse leadership that was provoked by verbal and psychological aggression was reported to lead to high burnout rates and emotional harm. The discoveries highlight the reality that such issues should be resolved by organizations through leadership development programs, feedback schemes and organizational cultures interventions to achieve healthier and more effective leadership practices. This is both a method of increasing interactivity of staff as well as preventing turnover and bringing work environment closer and more derailing by removing the dark side of leadership.